Electrochemically Induced Thiocyanation of Enaminones: Synthesis of Functionalized Alkenes and Chromones - Yang, Zan; Wang, Yanhong; Hu, Liping; Yu, Jiangjing; Li, An; Li, Lijun; Yang, Tao; Zhou, Congshan (Synthesis, 2020)
A simple and efficient electrochemically induced thiocyanation of enaminones under undivided electrolytic conditions has been developed. With this protocol, various polyfunctionalized alkenes and chromones could be obtained in good to excellent yields using readily available KSCN as the thiocyanation reagent under catalyst-, oxidant-, and transition-metal-free conditions.
Keywords: electrochemical reaction; thiocyanation; enaminones; oxidant free; catalyst free